Предмет: Алгебра,
автор: Slavarodin11
(c-4)(c+2)(c+3) в виде многочлена
Ответы
Автор ответа:
0
(с-4)(с+2)(с+3)=(с^-4с+2с-8)(с+3)=с в кубе--4с^+2с^-8с+3с^-12с+6с-24=с в кубе+с^-14с-24.
Автор ответа:
0
вложено==============
Приложения:
![](https://files.topotvet.com/i/9a8/9a8291d3738707fa4e809a856f31ce4b.jpg)
Похожие вопросы
Предмет: Физика,
автор: vilok80
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: Franchesko1
Предмет: Обществознание,
автор: helen1828